2019
DOI: 10.1177/1010428318823988
|View full text |Cite
|
Sign up to set email alerts
|

Role of discoidin domain receptor 2 (DDR2) and microRNA-182 in survival of women with high-grade serous ovarian cancer

Abstract: The objective of this study is to evaluate the relationship between discoidin domain receptor 2 (DDR2) and miR-182 expression with response to platinum-based chemotherapy and survival in women with high-grade serous ovarian cancer (HGSOC). We evaluated 78 women with HGSOC stages I-IV, diagnosed between 1996 and 2013, and followed up until 2016. DDR2 expression was assessed using immunohistochemistry on tissue microarray slides. The microRNAs were evaluated by qRT-PCR. DDR2 expression was high in 11 (14.1%) wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…The prognostic value of 172 protein biomarkers was evaluated by immunohistochemistry in 174 studies (Table 2). These markers are classified according to their biological functions, mainly including such functional pathways as EMT and metastasis [59][60][61][62][63][64][65][66][67][68][69][70][71], inflammation and immunity [72][73][74][75][76][77][78][79][80][81][82][83][84], antioxidant [85,86], angiogenesis [87][88][89][90][91][92][93][94][95][96][97][98][99], cell proliferation, migration and invasion [100][101][102][103][104]…”
Section: Tissue-based Prognostic Biomarkersmentioning
confidence: 99%
“…The prognostic value of 172 protein biomarkers was evaluated by immunohistochemistry in 174 studies (Table 2). These markers are classified according to their biological functions, mainly including such functional pathways as EMT and metastasis [59][60][61][62][63][64][65][66][67][68][69][70][71], inflammation and immunity [72][73][74][75][76][77][78][79][80][81][82][83][84], antioxidant [85,86], angiogenesis [87][88][89][90][91][92][93][94][95][96][97][98][99], cell proliferation, migration and invasion [100][101][102][103][104]…”
Section: Tissue-based Prognostic Biomarkersmentioning
confidence: 99%
“…MicroRNAs (miRs) represent a class of 21-23 nucleotides long small non-coding RNAs that can act as oncogenes (8) or tumor suppressors (9) in various types of cancer, including gastrointestinal (10), liver (11), pancreatic (12), ovarian (13), lung (14) and breast cancer (15). miRs can bind directly to the 3'-untranslated region (UTR) of target genes to negatively regulate protein expression (16).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the majority of involved studies were reported by authors in Asia (China, Japan, Taiwan, and South Korea), and the other studies were 1 from Canada, 3 from the USA, and 1 from Brazil. Moreover, 12 types of cancers including 3 ovarian cancers [5,7,9], 2 breast cancers [12,13], 1 osteosarcoma [16], 3 lung cancers [6,9,10], urological cancers (UC) which include 2 gallbladder carcinomas [17], 1 renal cancer [18], and 1 urothelial carcinoma [19], and gastrointestinal (GI) malignancies which include 1 gastric cancer [4], 2 HCCs [20,21], 1 esophageal cancer [22], 1 colorectal cancer [23], 1 pancreatic carcinoma [11], and 1 oral cell carcinoma [24] were evaluated in this meta-analysis. The total subjects registered were divided into high and low DDR groups based on the DDR measurement results.…”
Section: Literature Search and Data Characteristicsmentioning
confidence: 99%
“…DDRs are distributed in different organs; in solid tissues, DDR 1 is more expressed in epithelial cells, and DDR 2 is limited to mesenchymal cells [4]. Recently, studies have shown that the expression of DDRs upregulated in different types of malignancies such as hepatocellular carcinoma (HCC) [5,6], gastric cancer [4], ovarian cancer [5,7,8], lung cancer [6,9,10], pancreatic carcinoma [11], and breast cancer [12,13]. To the best of our knowledge, no systematic review and meta-analysis has been done to assess the relation between DDR expression and clinicopathologic features and prognostic value of DDRs in patients with different malignancies; so in this meta-analysis, we systematically pooled related published evidence to explain the prognostic significance of DDR expression in malignant tumors.…”
Section: Introductionmentioning
confidence: 99%